A Comparative Analysis of the Internationalisation Strategy of Chinese and Japanese Firms---The Case of Geely and Toyota - Jiang, Wenwen (2012)
In a long period of time, internationalisation has been related to MNEs from developed markets. For instance, after the World War II, the development of Japanese MNEs should be regarded as a “miracle”. Recently, the internationalisation of enterprises from emerging markets is on the rise. Considering the growth of Chinese MNEs, the development path after economic reforms in 1978 is similar to that of Japanese MNEs since World War II. As more Chinese enterprises start to be engaged in internationalisation, especially in mature market, a crucial issue should be addressed: whether Chinese MNEs will follow the steps of Japanese MNEs? Based on both the traditional international business models and Peng’s integrated framework, this dissertation will answer the question above. This study employs two case studies—Geely and Toyota, to illustrate the differences of internationalisation strategies between Chinese and Japanese MNEs in terms of expansion path and speed, entry mode, etc. An amount of research findings have emerged from this research. Firstly, the different industrial factors, resource features and institutional characteristics which lied in the growth background and competitive advantages would lead to the divergence of internationalisation strategies between Chinese and Japanese MNEs, especially in terms of expansion path and speed, preferred entry mode, etc. Secondly, the dissertation also examines the traditional models, including Dunning’s eclectic paradigm and the Uppsala model, which developed to explain internationalization of enterprises from developed economies. They may not have equal explanatory power for the internationalization of emerging market enterprises in the modern market. In contrast, Peng’s framework, as an integrated framework instead of complement or substitute of the traditional theories, is generally consistent with the internationalisation strategies of MNEs from both developed economies and emerging economies. Further, the boundaries of the research and future avenues for future research have also been identified in this dissertation.